2023
DOI: 10.3390/ijms24065249
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Metabolome Profiling Unveil Pigment Formation Variations in Brown Cotton Lines (Gossypium hirsutum L.)

Abstract: Naturally brown colored cotton (NBCC) is becoming increasingly popular due to its natural properties of coloration. However, poor fiber quality and color fading are key issues that are hindering the cultivation of naturally colored cotton. In this study, based on transcriptome and metabolome of 18 days post-anthesis (DPA), we compared the variations of pigment formation in two brown cotton fibers (DCF and LCF), with white cotton fiber (WCF) belonging to a near-isogenic line. A transcriptome study revealed a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…For instance, the identification of differential metabolites is employed to investigate the factors underlying the coloration of three distinct wheat grains, identifying cyanidin and peonidin as the principal anthocyanins responsible for color variation [ 16 ]. In the context of brown cotton fibers, most flavonoid-associated metabolites, such as myricetin, naringenin, catechins, epicatechin–epiafzelechin, and epigallocatechin, exhibit greater up-regulation than in white cotton fibers [ 17 ]. The composition and content of different flavonoid metabolites reveal the reasons for the flower color variation in Rhododendron pulchrum varieties [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the identification of differential metabolites is employed to investigate the factors underlying the coloration of three distinct wheat grains, identifying cyanidin and peonidin as the principal anthocyanins responsible for color variation [ 16 ]. In the context of brown cotton fibers, most flavonoid-associated metabolites, such as myricetin, naringenin, catechins, epicatechin–epiafzelechin, and epigallocatechin, exhibit greater up-regulation than in white cotton fibers [ 17 ]. The composition and content of different flavonoid metabolites reveal the reasons for the flower color variation in Rhododendron pulchrum varieties [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed a significant down-regulation of delphinidin-3-O-rutinoside in YTM compared with RTM, which may contribute to the diminished intensity of its red color. Epiafzelechin and lutein were also identified as the dominant factors in yellow pigments ( Lin et al., 2015 ; Lv et al., 2023 ). Similarly, our findings indicate a buildup of epiafzelechin and lutein in the YTM arils upon reaching maturity.…”
Section: Discussionmentioning
confidence: 99%